2019
DOI: 10.3389/fpsyg.2019.02369
|View full text |Cite
|
Sign up to set email alerts
|

Tell Me a Story: Socio-Emotional Functioning, Well-Being and Problematic Smartphone Use in Adolescents With Specific Learning Disabilities

Abstract: Although Specific Learning Disabilities (SLD) are described as specific difficulties in one or more academic areas, often socio-emotional problems are also reported to be related to well-being and school engagement. Moreover, recent evidence shows that emotional problems and reduced social support predict problematic use of new technologies, such as a smartphone, that can, in turn, increase these problems. In this study, we aimed to investigate socio-emotional functioning and its relation to well-being, school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…This is in line with the evidence that high-school students with specific learning disabilities (SLD) can develop adaptive strategies to deal with the school requests and focus on functional level of learning (Fenzi and Cornoldi, 2015). Accordingly, a recent work on the students with SLD included in this sample, focused on the impact of low literacy skills on well-being experience (Sarti et al, 2019) did not found any significant difference between clinical and control groups. On the contrary, students with SLD showed an increasing sense of thriving related to a growing trust and perceived support from others.…”
Section: Discussionmentioning
confidence: 71%
“…This is in line with the evidence that high-school students with specific learning disabilities (SLD) can develop adaptive strategies to deal with the school requests and focus on functional level of learning (Fenzi and Cornoldi, 2015). Accordingly, a recent work on the students with SLD included in this sample, focused on the impact of low literacy skills on well-being experience (Sarti et al, 2019) did not found any significant difference between clinical and control groups. On the contrary, students with SLD showed an increasing sense of thriving related to a growing trust and perceived support from others.…”
Section: Discussionmentioning
confidence: 71%
“…In most of the included studies ( k = 7, 77.8%), distribution of male and female participants was almost equal (50% ± 15%). One study, which compared two groups, had a higher amount of female participants (73.7%) in one of the groups, 32 while in another study the amount of male participants was 78.2% 33 . For an overview over the characteristics of included studies, see Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…It should be stated, however, that extreme human-likeness can result in the known uncanny valley effect, according to which HRIs are negatively influenced by robots that are too similar to the human (Mori, 1970;MacDorman and Ishiguro, 2006;Mori et al, 2012). Thus, the HSRs' appearance represents an important social affordance for HRIs, as further demonstrated by the psychological research on racial and disability prejudice (Todd et al, 2011;Macdonald et al, 2017;Sarti et al, 2019;Manzi et al, 2020b). The anthropomorphic features of the HSRs can increase humans' perception of humanness, such as mind attribution and personality, and influence other psychological mechanisms and processes (Kiesler and Goetz, 2002;MacDorman et al, 2005;Powers and Kiesler, 2006;Bartneck et al, 2008;Broadbent et al, 2013;ZƂotowski et al, 2015;.…”
Section: Anthropomorphismmentioning
confidence: 99%